Effectiveness of Tri-N-based unplugged coding instruction cards for figurative language learning in elementary schools - Nurul Faikoh; Akbar Al Masjid; Anang Sudigdo; Siti Anafiah; Dwi Susanto; Suhailee Sohnui (Rafandha Press, 2026)
Background: Majas learning plays an important role in increasing students' imagination, interpretation skills, and appreciation of literary texts. Majas learning is not only a linguistic skill but also a cognitive process that requires a deeper conceptual understanding. Based on field data, many students tend to rely on memorization rather than understanding the meaning and function of figurative expressions so that learning activities have not effectively facilitated students' conceptual understanding. Purpose: This study aims to examine the effectiveness of Tri-N-based unplugged coding instruction card media in improving students’ understanding of figurative language. Method: This study used a quantitative pre-experimental design with a one-group pretest–posttest model involving 75 fifth-grade students from three elementary schools. Data were collected through tests and analyzed using descriptive statistics, Shapiro–Wilk normality test, paired sample t-test, and N-Gain analysis. Findings: The results show that the mean score increased from 72.35 to 86.43, with a gain of 14.08 points. The paired sample t-test indicated a significant difference (p < 0.001), and the N-Gain score was 0.51 (moderate). These findings indicate that the media is effective in improving students’ conceptual understanding of figurative language.